Study on Formation of Chalk River Unidentified Deposits by Elemental Analysis of Metal Oxide Particles Deposited on Fuel Surface - Jung, Sang-Hyuk; Yun, Myung-Hee; Yeon, Jei-Won; Dal Park, Soon; Ahn, Hong-Joo; Choi, Jinsoo; Yang, Hoyeon; Song, Kyuseok (Asian Journal of Chemistry, 2012)
Chalk river unidentified deposits (CRUD) samples were obtained from nuclear fuels during the fuel cleaning process. The samples were analyzed by EPMA-EDS for evaluating the formation of CRUD. We observed that the CRUD composed of many particles with different shapes. In the samples, we selected three different particles and measured their elemental compositions. The compositions of the particles were Cr-Ni-Zn-Fe based oxide, Co-W-Cr mixed oxide and Zr oxide, respectively. From the analysis based on elemental composition, Cr-Ni-Zn-Fe mixed oxide was considered as the mixture of Ni-Zn ferrites and Ni-Zn chromites. And, from high content of Co and W, it was thought that metal dissolution and enrichment steps were included in the CRUD formation process. Finally, we confirmed ZrO2 layer could be removed from the fuel cladding during the fuel cleaning process.